3D antenna array for SWIPT Sensing with WPT capabilities - Pires, Diogo (2021)
In this work, the design and development of an alternative three-dimensional array is presented. This arrangement aims to improve Simultaneously Wireless Information and Power Transfer (SWIPT) systems and to provide advantages when integrated into a Wireless Sensor Network (WSN) architecture. The conceived 3D antenna array consists of eight antenna elements operating at 5.65 GHz that are attached in a 3D printed heptagonal prism. With this structure, it is intended to achieve as close as possible to an omnidirectional radiation pattern with considerable gain, avoiding power losses. The experimental measurements carried out are in line with the performed electromagnetic simulations and validate the array operation. A full azimuth coverage was ensured with an average realized gain of 6.7 dBi. For some azimuth directions, this gain can reach approximately 8.35 dBi. This array proves to be a reliable solution to fed multiple low-power sensors that are placed over the 360 azimuth angles.